Seasonal variation and prognosis in patients with acute myocardial infarction complicated by cardiogenic shock - Sodam Jung; Woo Jin Jang; Wang Soo Lee; Ik hyun Park; Ju Hyeon Oh; Jeong Hoon Yang; Hyeon-Cheol Gwon; Chul-Min Ahn; Cheol Woong Yu; Hyun-Joong Kim; Jang-Whan Bae; Sung Uk Kwon; et al. (Heliyon, 2024)
Background: Little is known about the association between seasonal variation and prognosis in patients with CS caused by AMI. Objectives: We investigated the 12-month clinical outcomes in patients treated with percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI) complicated by cardiogenic shock (CS) according to season. Methods: A total of 695 patients undergoing PCI for AMI complicated by CS was enrolled from 12 centers in South Korea. The study patients were divided into four groups according to season in which the AMI with CS occurred (spring, n = 178 vs. summer, n = 155 vs. autumn, n = 182 vs. winter, n = 180). We compared major adverse cardiovascular events (MACEs; the composite of cardiac death, myocardial infarction, re-hospitalization due to heart failure, and any revascularization) between the four groups. Results: The risk of MACE during the 12 months after CS was similar in the four groups: spring, 68 patients, vs. summer, 69, vs. autumn, 73, vs. winter, 68 (p = 0.587). Multivariate Cox-regression analysis revealed no significant difference in 12-month MACE among groups compared to the spring group after inverse probability of treatment weighting adjustment (summer, HR 1.40, 95 % CI 0.98–1.99, p = 0.062; autumn, HR 1.26, 95 % CI 0.89–1.80, p = 0.193; winter, HR 1.18, 95 % CI 0.83–1.67, p = 0.356). The similarity of MACE between the four groups was consistent across a variety of subgroups. Conclusions: After adjusting for baseline differences, seasonal variation seems not to influence the mid-term risk of 12-month MACE in patients treated with PCI for AMI complicated by CS. Condensed abstract: Data are limited regarding the association between seasonal variation and prognosis in patients with cardiogenic shock (CS) caused by AMI. This study divided patients undergoing PCI for AMI complicated by CS into four groups based on the season of occurrence and found no significant differences in 12-month MACE between the groups after adjusting for bias and confounding factors. Multivariate analysis revealed consistent MACE similarity across subgroups. The study suggests that seasonal variation has no impact on the mid-term risk of 12-month MACE in patients with CS caused by AMI, after adjusting for baseline differences. Trial registration: ClinicalTrials.gov NCT02985008RESCUE (REtrospective and prospective observational Study to investigate Clinical oUtcomes and Efficacy of left ventricular assist device for Korean patients with cardiogenic shock), NCT02985008, Registered December 5, 2016 - retrospectively and prospectively. Irb information: This study was approved by the institutional review board of Samsung Medical Center (Reference number: 2016-03-130).